Peran Mediasi Perceived Organizational Support pada Pengaruh Self Efficacy Terhadap Employee Green Behavior: Studi pada Karyawan PT. Massindo Solaris Nusantara - Given Ray T. Yahya; Andi Yusniar Mendo; Rezkiawan Tantawi (Economic Reviews Journal, 2025)
This Study aimed to determine the role of perceived organizational support mediation on the effect of self efficacy on omployee green behavior (study on employees of PT Massindo Solaris Nusantara). This study used 70 sampels equal to the population (total sampling) taken using non probability sampling techniques. The data in this study were collected through a questionary and studied through path analysis assisted by the SPSS 22 application. Based on the analysis, self efficacy had a positive and signifcant effect on employee green behavior and perceived organizational support. Meanwhile, perceived organizational support had a positive and significant effect on employee green behavior and acted as a partial mediator on self efficacy and employee green behavior.